2018
DOI: 10.1080/00913847.2018.1462083
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder and elbow injuries in soccer goalkeepers versus field players in the National Collegiate Athletic Association, 2009–2010 through 2013–2014

Abstract: Shoulder and elbow injuries in NCAA soccer players are significantly more common in goalkeepers than field players. Incidence varies widely by position and injury, with a number of associated risk factors. Soccer players sustaining these injuries, along with their coaches and medical providers, may benefit from this injury data to best manage expectations and outcomes. Soccer governing bodies may use this to track injury incidence and response to preventative measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 19 publications
4
35
0
3
Order By: Relevance
“…Previous literature suggests that injuries are most likely to occur in the setting of competition and during in-season play. 4,9,10 These findings were consistent with results of our analysis, which suggested a significant 3.5-times higher injury rate during competition than practice and higher IRRs for in-season events. Contact was the most common injury mechanism, comprising 67% of total injuries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous literature suggests that injuries are most likely to occur in the setting of competition and during in-season play. 4,9,10 These findings were consistent with results of our analysis, which suggested a significant 3.5-times higher injury rate during competition than practice and higher IRRs for in-season events. Contact was the most common injury mechanism, comprising 67% of total injuries.…”
Section: Discussionsupporting
confidence: 91%
“…5,16 Literature specifically discussing NCAA football players has reported a higher overall incidence as well—13.20 per 10,000 AEs. 10 The injury rate reported in the baseball-specific literature is an order of magnitude higher than our all-athletes overall rate of 1.76 injuries per 10,000 AEs. However, the prior football literature has reported rates comparable with the rates in our study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Some studies have investigated shoulder injuries in soccer players, regardless of the playing level, with a primary interest in goalkeepers. 5,11,19,26 In addition, a number of studies have reported on soccer-related injuries seen in emergency departments. 16,17,23,25,27 For example, Sytema et al 25 described that upper extremity injuries constituted 27% of all soccer injuries seen at an emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…High-performance sport is one of the national priorities whose successful implementation requires the establishment of athlete training and support systems [1][2][3][4][5]. A medical screening system is mainly focused on the identification and management of conditions, while substantially less attention is paid to the study of the capacity of the athlete's body to adapt to extreme loads [1][2][3][4][5]. Conventionally, the adaptation includes all the types of congenital and acquired adaptive activities implemented at cellular, systemic, and organismic levels [6,7].…”
Section: Introductionmentioning
confidence: 99%